The Emergence of Caring Economics-Based Entrepreneurship Learning Model in Islamic Higher Education - Efiyanti, Alfiana Yuli; Pusposari, Luthfiya Fathi; Sari, Ulfi Andrian (Fakultas Tarbiyah dan Ilmu Keguruan Institut Agama Islam Negeri Kerinci, 2024)
To fulfill their needs, humans often exploit available resources without considering the values of fairness and concern for the surrounding environment Hence, it is imperative to take tangible steps to promote more prudent practices in the management of resources. The study focuses on three Islamic Higher Education Institutions (PTKIs) in Indonesia that incorporate Islamic values into their courses, including Entrepreneurship. The informants consisted of 9 entrepreneurship course lecturers and 20 students enrolled in the course. Data were obtained through open surveys and in-depth interviews. This research reveals that the entrepreneurship learning in PTKIs focuses solely on enhancing the quality and quantity of production, expanding product distribution, and attracting more consumers, ultimately leading to higher profits. There is an urgent need to develop an entrepreneurship learning model based on caring economics. This research recommends further studies to develop an entrepreneurship learning model based on caring economics.